(untitled) (Journal of Parents and Teachers, 2014)
The article makes a profound reflection on the work and pillars of the school. To this end, it outlines the social panorama in which this institution is inscribed while analyzing various factors that endow it with knowledge and value. A key element that appears throughout the article is evaluation as an indispensable tool and backbone of the teaching and learning process. In this context, the author analyzes the work of the teacher not only from a didactic but also from an ethical point of view, relating it in an integral way with the evaluation process